Regional features of building museum exhibits on history of the modern Russo-Ukrainian War - Юрій Бураков; Лілія Питльована (Cхід)
Various aspects of constructing stationary and mobile museum expositions of Ukraine in different regions of the country are analyzed, with the purpose of creating permanent exhibitions on the history of the modern Russo-Ukrainian War. The positive experience in organizing the preservation and popularization of the Russo-Ukrainian War monuments in the capital and regional museums of Ukraine is summarized, as well as the processes of their exposition and exhibition activity transformation at the current stage are studied. It is noted that the significance of constructing expositions on the modern history of Ukraine and the exhibition activities of national museums increased in connection with the Russia-Ukraine war of 2014 - 2023, when exposition materials became not only a means of forming historical memory, but also a source of patriotism and loyalty to national priorities, an important factor in formation of the Ukrainian nation. Individual exhibitions are studied in the “National Museum on the History of Ukraine in the Second World War”, “Memorial Complex”, "National Museum of the History of Ukraine", "National Military Historical Museum", regional local history museums, museums of higher military educational institutions, garrison museums. The study emphasizes the relevance of creating virtual means of presenting the historical past and present. The opening of virtual exhibitions and expositions in Ukraine is promising, as it connects a large audience both in our country and abroad with the exhibition ma-terial and unique funds. Foreign presentations have become an important field in modern expositions presentations. This applies both to the work of individual museums and individual foundations, European and global press centers, individual foundations, etc. A conclusion is made about the accumulated rich experience of the museums of Ukraine in all spheres of activity and, primarily, the active use of museum collections in the national and patriotic education of our country’s youth.